2004
DOI: 10.1177/1073858404263526
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Substrates of Reward Processing in Humans: The Modern Role of fMRI

Abstract: Experimental work in animals has identified numerous neural structures involved in reward processing and reward-dependent learning. Until recently, this work provided the primary basis for speculations about the neural substrates of human reward processing. The widespread use of neuroimaging technology has changed this situation dramatically over the past decade through the use of PET and fMRI. Here, the authors focus on the role played by fMRI studies, where recent work has replicated the animal results in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
272
3
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 413 publications
(305 citation statements)
references
References 56 publications
21
272
3
7
Order By: Relevance
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 85%
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 85%
“…This underlines views of its function of a more general role in emotion processing as for emotional arousal or intensity without a valence specificity (Baxter and Murray, 2002;Anderson et al, 2003;Gottfried et al, 2003;McClure et al, 2004).…”
Section: Anatomical and Functional Features Of The Revealed Areasmentioning
confidence: 54%
“…In parallel, amygdalar activation as an indicator for emotional arousal (McClure et al, 2004) was diminished during affect labeling of external cues with increasing mindfulness . Novices in mindfulness strategies showed functional connectivity between MPFC and insula (Farb et al, 2007), the latter indicating an association with bodily signals (Critchley et al, 2004).…”
Section: Emotion Introspection and Clinical Implicationsmentioning
confidence: 95%